Use of last generation electronic device for the experimental computation of the convection coefficient over a flat aluminum plate - Ramírez-González, Luis Diego (2019)
This article deals with a jet of air at a lower temperature than the environment, which discharges onto a flat aluminum plate located over a matrix of sensors that measures the temperature in the area of ​​impact. Subsequently, characteristic curves are found for each height and diameter ratio of the jet (H/D), through data processing. The coefficient of convection is determined using the relationship between the slope of the graph together with the result from the temporal evolution of the temperature.The main objective of the work is the verification of the functionality of the advanced electronic device, which is carried out successfully. Also, and using visualization techniques the behavior of the jet is analyzed. Both the electronic device and the use of air jets have great interest in the industry (refrigeration, heating, drying processes, cleaning among others). In the case of the advance electronic device it is possible to provide data regarding real-time temperature measurement in areas of difficult access.